Psychological assessment : a problem-solving approach - Suhr, Julie A. (Evidence-based practice in neuropsychology)
"This authoritative clinical reference and text provides a complete guide to conducting empirically based assessments to support accurate diagnoses and better clinical care. The book builds crucial skills for gathering and interpreting data for specific assessment purposes. It also presents more advanced ways to integrate information from tests, interviews, observations, and other sources, within a biopsychosocial framework that fully addresses the needs of each client. Particular attention is given to accounting for potential biases that affect every stage of the decision-making process. User-friendly features include case examples, advice on writing reports and giving feedback to clients, and a detailed sample report"--